Analysis of defects in additively manufactured lattice structures - Echeta, Ifeanyichukwu (2023)
Additive manufacturing is a popular area of research because it greatly increases design opportunities, allowing for significantly more geometric freedom than in more established manufacturing methods, such as machining, casting and forming. A relatively small set of additive manufacturing processes are consistently used for the manufacturing of lattice structures, and these processes produce characteristic defects and geometric deviations within lattice structures.